Measuring the Role of Image Representation in Generating Misconceptions Related to Plate Tectonics - Haas, Brady J. (My University, 2011)
Previous studies have indicated that post-secondary students possess a range of alternative conceptions regarding plate tectonics. The goal of this study was to determine the effectiveness of a novel plate tectonics image that was specifically designed to minimize potential misconceptions.
Color poster with text, images, and graphs.
Keywords: Plate tectonics; Visual perception--Analysis; Geological Society of America--Surveys; Posters